Soft tissue profile analysis using Ioiâs method for dentoalveolar bimaxillary protrusion cases before and after treatment with extractions of four first premolars - Ziliwu, Yuliana; Hambali, Tono S.; Salim, Jono; Mardiati, Endah (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The purpose of this study is to measure the soft tissue profile changes before and after treatment of dento-alveolar bimaxillary protrusion cases which had orthodontic treatment including extraction of upper and lower first premolars. Ioris soft tissue analysis used in this study and cephalometric analysis on 14 patients wich fulfilled sample criteria was performed. Four angular and two linear measurements were done manually utilizing protractor. Statistical analysis was paired t-test. The result showed significant changes in soft tissue after the treatment.